The Predictive Value of Health Anxiety for Cancer Incidence and All-Cause Mortality: A 44-Year Observational Population Study of Women. Issue 2 (February 2021) - Sigström, Robert; Hällström, Tore; Waern, Margda; Skoog, Ingmar
ABSTRACT: Objective: Long-term data concerning mortality and serious illness as a function of health anxiety are scarce. We aimed to study health anxiety in relation to long-term mortality and cancer morbidity among women. Methods: A Swedish population sample of women ( n = 770; ages, 38–54 years) took part in a general medical and psychiatric examination in 1968 to 1969 and were followed up until 2013 in national Swedish registries for all-cause mortality and first diagnosis of cancer. A modified version of the Whiteley Index questionnaire (maximum score, 12) was used to measure health anxiety. Scores were trichotomized based on quartiles as no (score 0, lowest quartile), mild-moderate (score 1–2, middle quartiles), and high (score ≥3, highest quartile) health anxiety. Risks of death and cancer were evaluated with Cox regression models. Results: Compared with women with mild-moderate health anxiety levels, women with no health anxiety had a higher risk of death (age-adjusted hazard ratio [HR] = 1.22, 95% confidence interval [CI] = 1.00–1.49; fully adjusted for baseline sociodemographic, mental, and physical health variables: HR, 1.44, 95% CI = 1.17–1.76). Women with high health anxiety levels had a greater risk of death in age-adjusted analysis (HR = 1.26, 95% CI = 1.04–1.54; fully adjusted HR = 1.21, 95% CI = 0.98–1.49). For both groups, the mortality risk was time dependent and declined during follow-up. We observed no between-group differences in the risk of cancer. Conclusions: In this population-based cohort of midlife women, health anxiety was moderately associated with mortality in a U-shaped fashion. Absence of health anxiety entailed the greatest risk when other factors were taken into account. Abstract : Supplemental digital content is available in the text.